2021
DOI: 10.35967/njip.v20i1.169
|View full text |Cite
|
Sign up to set email alerts
|

Menilai Kualitas Pilkada dalam Era Pandemi

Abstract: Penelitian ini bermaksud untuk menjelaskan dan mengelaborasi tentang kualitas Pilkada pada era pandemi yang diselenggarakan di Kabupaten Indragiri Hulu Tahun 2020. Pilkada yang dilakukan pada Tahun 2020 ini sangat berbeda dari Pilkada sebelumnya karena mendapatkan ancaman dari penyebaran pandemi COVID-19. Oleh karena itu, menarik untuk menilai kualitas Pilkada di Kabupaten Indragiri Hulu dalam masa pandemi ini. Penelitian ini menggunakan pendekatan kualitatif dengan sumber informasi dari informan penelitian, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Namun, disisi lain masih terdapat hasil positif dalam penyelenggaraan Pilkada yaitu meningkatkan partisipasi politik masyarakat dalam menggunakan hak pilihnya. Kendatipun belum memenuhi prinsip-prinsip Pemilu yang berkualitas dan berintegritas (Hasanuddin et al, 2021. Negara demokrasi memungkinkan lahirnya politik dinasti. Indonesia sebagai negara demokrasi harus menerima konsekuensi tersebut.…”
Section: Pendahuluanunclassified
“…Namun, disisi lain masih terdapat hasil positif dalam penyelenggaraan Pilkada yaitu meningkatkan partisipasi politik masyarakat dalam menggunakan hak pilihnya. Kendatipun belum memenuhi prinsip-prinsip Pemilu yang berkualitas dan berintegritas (Hasanuddin et al, 2021. Negara demokrasi memungkinkan lahirnya politik dinasti. Indonesia sebagai negara demokrasi harus menerima konsekuensi tersebut.…”
Section: Pendahuluanunclassified
“…Hasanuddin, et al, showed that the violations that occurred during the Regional Head Election campaign in Indragiri Hulu were even more significant during the Covid-19 pandemic. 9 Affandi & Affandi point out that the violations during the Regional Head Election campaigns in Depok and Sukabumi were due to mass mobilization exceeding the amount determined based on Regulation of General Election Commission No. 13 of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…10 of 2016 concerning Regional Head Elections prohibits using the SARA issue to give up one of the regional head candidates, the SARA issue still arises when the regional elections are held (Rama, 2020). In addition, the simultaneous regional elections in 2019 increased political participation from the public, but money politics also strengthened (Hasanuddin et al, 2021). Researchers from the Constitution and Democracy Initiative explained that SARA politics and the neutrality of civil servants, TNI and Polri became an obstacle or problem in general elections.…”
Section: Introductionmentioning
confidence: 99%